PATHFIT 2 : physical activities towards health and fitness 2 - Toldoya, Jacklyn Anne D.; Conlu, Arlene A.; Tiu, Sherwin Ryan G.; Pulanco, Katrina Christian Barnard T. (Malabon City : Mutya Publishing House, 2024)
"This book provides an in-depth discussion of what Physical Activities Towards Health and Fitness 2 (PATHFit 2) Exercise-Based Fitness Activities course is all about. It is designed after the CMO no. 39 s. 2021 where it builds on the foundation of motor skills through core training. Students will experience a variety set of exercise programs patterned after the different components of physical fitness for the purpose of maintaining and enhancing cardiorespiratory endurance and musculoskeletal fitness."
Includes references.
English.
Keywords: Physical education; Physical fitness